A case of incisional hernia repair using Composix mesh prosthesis after antethoracic pedicled jejunal flap reconstruction following an esophagectomy - Atsushi Yasuda; Takushi Yasuda; Hiroaki Kato; Mitsuru Iwama; Osamu Shiraishi; Yoko Hiraki; Yumiko Tanaka; Masayuki Shinkai; Motohiro Imano; Yutaka Kimura; Haruhiko Imamoto (Surgical Case Reports, 2017)
Abstract Background An incisional hernia in a case of antethoracic pedicled jejunal flap esophageal reconstruction after esophagectomy is a very rare occurrence, and this hernia was distinctive in that the reconstructed jejunum had passed through the hernial orifice; a standard surgical treatment for such a presentation has not been established. Herein, we describe a case of repair using mesh prosthesis for an atypical and distinctive incisional hernia after antethoracic pedicled jejunal flap esophageal reconstruction. Case presentation A 77-year-old woman with a history of subtotal esophagectomy who had undergone antethoracic pedicled jejunal flap reconstruction complained of epigastric prominence and discomfort without pain. On examination, she had an abdominal protrusion between the xiphoid process and the umbilicus that contained the small bowel. Computed tomography showed that the fenestration of the abdominal wall that was intentionally created for jejunum pull-up was dehisced in a region measuring 9 × 15 cm and the small intestine protruded through it into the subcutaneous space without strangulation. Because the hernial orifice was too large and the reconstructed jejunum was passing through the hernial orifice in this case, we applied a parastomal hernia repair method that was modified from the inguinal hernia repair using the Lichtenstein technique. After 3 years and 5 months following surgery, the patient has recovered without hernia recurrence or other complications. Conclusion We consider this to be the first case of repair using Composix mesh prosthesis for repair of an atypical and distinctive incisional hernia after an antethoracic pedicled jejunal flap reconstruction. This method seems to be useful and could potentially be widely adopted as the surgical treatment for this condition.